Adriatic Tyrrhenian. On the relations between a marquis Hugh, Pomposa, and the Po Delta area (around the year 1000) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2024)
The article takes as its starting point a specific case study: the donation of a marquis Hugh to Santa Maria di Pomposa, recorded in the series of imperial diplomas for the monastery from 1037 onwards, and more broadly the relationships between marquises, many of whom bore the same name (Hugh), and important monastic institutions in the Po delta, established between the 10th and 11th centuries. The close analysis of this case is intended to offer a methodological reflection on the making and structuring of the lists of possessions embedded in the text of the diplomas and their use as a historical source. Furthermore, the aim is to contribute to the questioning of patterns of thought that have been influenced by the categories of the Old-Regime statehood and nobility by answering the following questionnaire. What did it mean to be a marquis in the Kingdom of Italy between the 10th and 11th centuries? What were the spheres and forms of action and relationship of these individuals?
Keywords: Middle Ages, 10th-11th century, Italy, monasteries, marquises, diplomas